Ecological studies and analysis of glucomannan content in selected amorphophallus spp. of Peninsular Malaysia / Dahlia Shahbuddin - Shahbuddin, Dahlia (2012)
A study was conducted to investigate the ecological parameters and glucomannan content of selected Amorphophallus spp. in Peninsular Malaysia. A survey and documentation of Amorphophallus spp. were carried out throughout Peninsular Malaysia and the ecological parameters were measured and quantified. The life cycle of A. paeoniifolius was studied over a period of one year and two locations, namely Jerantut, Pahang and Kuala Kangsar, Perak were selected for quadrat analysis of A. paeoniifolius and A. prainii. Samples of four Amorphophallus spp. were collected for determination of glucomannan content following the method by Megazyme International Ireland Limited (2004) and Wang et. al. (1998). A total of six species namely A. bufo, A. elatus, A. elegans, A. oncophyllus, A. paeoniifolius and A. prainii were successfully collected and documented. The species are distributed mainly in disturbed secondary forests and near forest margins. While A. paeoniifolius and A. prainii are common throughout Peninsular Malaysia, A. bufo, and A. oncophyllus are restricted in distribution, such as the highlands and northern part of Peninsular Malaysia respectively. From the field study, it was observed that the optimum growth of Amorphophallus species in Peninsular Malaysia can be achieved when the humidity range was between 53 to 85 %. Result from this study indicated that Amorphophallus species could grow at locations with high light intensity of up to 2780 Lux. Amorphophallus spp. appeared to thrive best at temperatures between 25 -30°C. Results also indicated that all Amorphophallus species were tolerant to soil acidity and require a fertile soil with optimum moisture content of 20-25%. Study on the life cycle of A. paeoniifolius showed that the plant undergoes 3 phases in its life cycle which was vegetative growth phase, followed by a dormant phase and subsequently the generative growth phase. Quadrat analysis showed that Amorphophallus spp. can grow well under the orchard canopy with a little shade from direct sunlight. The Importance Value (IV) of Amorphophallus species varied considerably with season for Jerantut and Kuala Kangsar. The Importance Value (IV) was highest during season 3, (September - December), followed by Season 2 (May - August) and lowest during Season 1 (January - April). The pattern of IV coincided well with the climatic conditions. Amorphophallus spp. go through dormancy period in dry season (season 1), whereby the IV was highest when both locations were experiencing slightly lower temperature, higher humidity and rainfall in season 3. The result of the glucomannan (GM) study indicated that A. oncophyllus had the highest GM content (58.65 %); followed by mature A. paeoniifolius (50.22%); mature A. prainii (29.71 %); A. elegans (17.01 %); young A. paeniifolius (14.90 %); and young A. prainii (9.23 %). Significance difference in GM content of original corm is approximately 15-18 % higher as compared to transplanted corm. This could be due to some physiological changes during the process of transplanting. The study also showed that the GM content was high in matured corms than in young corms and different at certain growing period. It can be concluded that Amorphophallus species in particular A. paeoniifolius and A. oncophyllus have great potential to be commercialized in Malaysia. The plants can provide economic levels of glucomannan (GM) in the corm. They are easy to grow under the various types of soil and climatic conditions in Peninsular Malaysia. However, Amorphophallus species require certain climatic and ecological conditions to develop the optimum GM content for commercialization.